Psychopathology and mental distress : contrasting perspectives / Jonathan D. Raskin. - Raskin, Jonathan D. (Bloomsbury Academic, 2024)
This core textbook offers a comprehensive overview of different approaches to the causes, assessment and treatment of psychological disorders. It includes important diagnostic frameworks, including the new DSM-5-TR, ICD-11 and PDM, but also widens the scope of coverage beyond mainstream psychiatric models to include psychological, biological, historical, sociocultural and therapeutic approaches. Contemporary and well-balanced, it provides an even-handed and holistic foundation, allowing students to develop a strong critical mindset while retaining a robust research-driven orientation.